Constraints of Cultural Transfer in Teaching Indonesian Language as a Foreign Language (BIPA) - Lina Herlina (Eastasouth Institute, 2023)
This study aims to describe and explain what obstacles are encountered in cultural transfer in teaching Indonesian Language as a Foreign Language (BIPA). This study uses a qualitative research method with a descriptive approach. The results show that the barriers to cultural transfer in teaching BIPA include a) cross-culture, b) the use of bilingualism by Indonesians, c) the limited ability of foreign students to speak Indonesian at the elementary level, d) the tempo of Indonesian people's speech, e) limited knowledge of the teachers about culture, f) the limitations of cultural integration in learning, g) there is no demand for a special evaluation of cultural understanding, and h) the lack of foreign students’ motivation.